Kenya - Kabaune village - Giaki - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Farmer from Kenya working in the field with his cattle. Adapting to the changing climate in Kenya is crucial in order to sustain farming and the livelihoods that come with it. Andrew Gitari from Kabaune village in Kenya talks in the video series "Farmer Testimonials" about how the reduction of trees also lead to water losses.